Small Non-Coding RNAs: New Insights in Modulation of Host Immune Response by Intracellular Bacterial Pathogens - Ahmed, Waqas; Zheng, Ke; Liu, Zheng-Fei (Frontiers in Immunology, 2016)
Pathogenic bacteria possess intricate regulatory networks that temporally control the production of virulence factors, and enable the bacteria to survive and proliferate within host cell. Small non-coding RNAs (sRNAs) have been identified as important regulators of gene expression in diverse biological contexts. Recent research has shown bacterial sRNAs involved in growth and development, cell proliferation, differentiation, metabolism, cell signaling and immune response through regulating protein–protein interactions or via their ability to base pair with RNA and DNA. In this review, we provide a brief overview of mechanism of action employed by immune-related sRNAs, their known functions in immunity, and how they can be integrated into regulatory circuits that govern virulence, which will facilitates to understand pathogenesis and the development of novel, more effective therapeutic approaches to treat infections caused by intracellular bacterial pathogens.